(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2013)
The main highlight of Bisphenol-A (BPA) is the exhibition of the estrogenic properties, which is found to be a threat to human beings. This mini review summarizes available data in the literature (1997–2011) on toxicity effect of BPA in several animal studies. There are needs of more validated studies to be carried out to determine the toxicity effects of BPA on human beings.